Short-term effects of food price shocks ensuing expiration of the Black Sea Grain Deal: A food security simulation - Momanyi, Dorah Kwamboka. (CGIAR, 2023)
Russia’s invasion of Ukraine has disrupted agriculture and trade, jeopardizing global food security, and, along with other factors, causing food prices to skyrocket globally – especially for wheat.